Characterization of RP1L1, a highly polymorphic paralog of the retinitis pigmentosxa 1 (RP1) gene - HUMPHRIES, PETER (Molecular Vision, 2003)
PURPOSE: To determine the full-length sequence of a gene with similarity to RP1 and to screen for mutations in this newly characterized gene, named retinitis pigmentosa 1-like 1(RP1L1). Since mutations in the RP1 gene cause autosomal dominant retinitis pigmentosa, it is possible that mutations in RP1's most sequence similar relative, RP1L1, may also be a cause of inherited retinal degeneration. METHODS: A combination of cDNA clone sequencing, RACE, and database analysis were used to determine the RP1L1 mRNA sequence and its genomic organization. PCR analysis, semi-quantitative RT PCR, and in situ hybridization were used to determine the expression pattern of RP1L1. Single-strand conformational analysis and automated sequencing were used to screen probands from 60 adRP families for potential disease-causing mutations in RP1L1. RESULTS: The human RP1L1 gene is encoded in 4 exons, which span 50 kb on chromosome 8p. The length of the RP1L1 mRNA is large, over 7 kb, but its exact length is variable between individuals due to the presence of several length polymorphisms, including a 48 bp repeat. RP1L1 encodes a protein with a minimal length of 2,400 amino acids and a predicted weight of 252 kDa. Expression of RP1L1 is limited to the retina and appears to be specific to photoreceptors. Mutational analysis of 60 autosomal dominant retinitis pigmentosa probands revealed the presence of 38 sequence substitutions in RP1L1. Over half of these substitutions result in alteration of the RP1L1 protein, but none of these substitutions appear to be pathogenic. CONCLUSIONS: The RP1L1 gene encodes a large, highly polymorphic, retinal-specific protein. No RP1L1 disease-causing mutations were identified in any of the samples tested, making it unlikely that mutations in RP1L1 are a frequent cause of autosomal dominant retinitis pigmentosa. Additional experiments will be needed to determine if mutations in RP1L1 cause other forms of inherited retinal degeneration.
PUBLISHED
Keywords: Ophthalmology